(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article examines the political career of former German Chancellor Angela Merkel, her major reforms, and their impact on both Germany and the European Union. It provides a comprehensive analysis of Merkel’s pragmatic leadership style, her approach to economic stability, migration policy, energy transition, and crisis management during the COVID-19 pandemic. The study highlights both positive and critical perspectives on her legacy using practical examples.